Psychological Well-being of Early Adolescents from Divorced Families: The Role and Necessity of Family Counseling Therapy - Romina A. Danguilan; Enrique T. Ona; Nemma N. Evangelista; Robert G. Ejercito (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Parental divorce significantly impacts the psychological well-being of early adolescents, often leading to emotional instability and strained relationships. Despite existing research, the effects on their mental health across various dimensions remain underexplored. Objective: This study aims to describe the psychological well-being of early adolescents from families with a history of broken homes. Method: The research method used in this study is a case study, conducted in 2024. The study involved four subjects, and data were collected through interviews and observations. Data analysis followed the interactive analysis model proposed by Miles and Huberman, and data validation was conducted through triangulation and credibility tests in two stages. Result: The results showed that early adolescent individuals who experienced parental divorce in the past exhibited diverse outcomes across each dimension of psychological well-being. Conclusion: This study offers valuable insights into how early adolescents from broken-home families experience varying levels of psychological well-being across different dimensions. Contribution: This research serves as a source of knowledge about the psychological conditions of early adolescents from broken-home families, highlighting the varied effects of parental divorce on their psychological well-being.